On Strike: Six Key Labour Struggles in Canada, 1919-1949 - Abella, Irving (James Lewis & Samuel Publishers, 1974)
[This book] focuses on six important - but largely unknown - strikes where Canadian workers fought the combined forces of capital and government for basic union rights and for decent wages and working conditions. The strikes described - the Winnipeg 1919 general strike, Estevan 1931, Stratford 1933, Oshawa 1937, the Ford Windsor strike of 1945, and Asbestos 1949 - were all major events in Canadian labour and political history. They demonstrate the strength of the labour movement, and they show the willingness of governments to use police, troops, intimidation and violence in attempts to break strikes and crush unions. --Publisher's description. Contents: Introduction. The Winnipeg General Strike / David Bercuson -- Estevan, 1931 / S.D. Hanson -- Aid to the civil power: the Stratford strike of 1933 / Desmond Morton -- Oshawa 1937 / Irving M. Abella -- Ford, Windsor, 1945 / David Moulton -- Asbestos 1949 / Fraser Isbester.
Keywords: Labour Movement; Strikes; Unions